Upaya Menumbuhkan Jiwa Kewirausahaan Melalui Bazar Festival Numerasi di SD Negeri Plumpungrejo 02 - Gita Wahyu Ningsih; Yekti Condro Winursito (BADAN PENERBIT STIEPARI PRESS, 2023)
Bazaar is one of the strategies and innovation activities that support the entrepreneurship sector. Entrepreneurship itself is one of the aspects that support the improvement of the economy of a region an area. Increasing the economy of a region must of course be balanced with creativity and existing resources. Therefore, instilling the spirit of entrepreneurship from an early age is one of the efforts to optimize human resources. human resources. So that through this numeration festival bazaar can be a means to train students' entrepreneurial spirit from an early age.a means to train the entrepreneurial spirit of students from an early age. Methods in this community service activity this community service activity is to use a mentoring method that is based on PAR (Participatory Action Research). The use of this method is considered effective because researchers take part and have an important role in the activities studied that was researched. The results achieved from this community service activity are students starting to have an entrepreneurial spirit have an entrepreneurial spirit. Students can develop their creativity in selling products and this activity also supports UMKM in the Plumpungrejo 02 State Elementary School area.